2020
DOI: 10.1371/journal.pone.0237614
|View full text |Cite
|
Sign up to set email alerts
|

A brief questionnaire measure of multidimensional schizotypy predicts interview-rated symptoms and impairment

Abstract: The present study employed structured diagnostic interviews to assess the construct validity of the brief version of the Multidimensional Schizotypy Scale (MSS-B), which was developed to assess positive, negative, and disorganized dimensions of schizotypy. It was hypothesized that the MSS-B subscales would be associated with differential patterns of symptoms and impairment, comparable to findings for the full-length MSS. A total of 177 young adults completed structured diagnostic interviews assessing symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
37
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 14 publications
(52 citation statements)
references
References 44 publications
13
37
2
Order By: Relevance
“…To determine the sample size, we reviewed effect sizes from comparable cross-sectional interview studies of schizotypy, relying primarily on Kemp et al (2021) as they used comparable measures, design, and sampling procedures as the present study. Most of our hypothesized effects had medium-to-large effect sizes in previous studies, although they ranged from small (f 2 = .07 for positive schizotypy predicting paranoid personality traits) to large (f 2 = .75 for negative schizotypy predicting schizoid personality traits).…”
Section: Methods Power Analysis and Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine the sample size, we reviewed effect sizes from comparable cross-sectional interview studies of schizotypy, relying primarily on Kemp et al (2021) as they used comparable measures, design, and sampling procedures as the present study. Most of our hypothesized effects had medium-to-large effect sizes in previous studies, although they ranged from small (f 2 = .07 for positive schizotypy predicting paranoid personality traits) to large (f 2 = .75 for negative schizotypy predicting schizoid personality traits).…”
Section: Methods Power Analysis and Participantsmentioning
confidence: 99%
“…This is relevant because recent questionnaire (Kemp et al, 2018) and ambulatory assessment (Kwapil et al, 2020) studies indicated that when positive, negative, and disorganized schizotypy are used as simultaneous predictors, constructs that were previously associated with positive schizotypy appear better accounted for by disorganized schizotypy, such as negative affect, emotional dysregulation, and cognitive-behavioral disorganization (Oezgen & Grant, 2018). Kemp et al (2021) examined the association of the three schizotypy dimensions using the Multidimensional Schizotypy Scale (MSS; with interview measures of symptoms and impairment, including assessment of Cluster A personality disorders diagnoses and traits. Consistent with previous findings, they reported that positive schizotypy was associated with elevated schizotypal and paranoid traits and inversely with schizoid traits, whereas negative schizotypy was associated with elevated schizotypal, schizoid, and paranoid personality disorder traits.…”
Section: Schizotypy and Personality Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…The MSS-B was introduced in the protocol assessment once the sampling had already started, so only 59 (40 college and 19 technical school students) participants have data for the MSS-B. Of note, the MSS-B has demonstrated to overcome limitations associated with existing measures of schizotypy such as unclear conceptual framework, outdated items, ethnical/sex differences, or exclusion of disorganized schizotypy and to show good internal reliability and construct validity ( 83 , 84 ). Data of the MSS-B for the disorganized dimension (Cronbach alpha = 0.75) and the factorially-derived dimensional scores based on the WSS for the positive and negative dimensions were used.…”
Section: Methodsmentioning
confidence: 99%
“…Association of the MSS-B subscales with interview measures of symptoms and impairment. Kemp, Bathery, Barrantes-Vidal, and Kwapil (2020) assessed the associations of the MSS-B positive, negative, and disorganized schizotypy subscales with interview-rated symptoms and impairment in 177 young adults. As hypothesized, the MSS-B positive schizotypy subscale was associated with interview-rated positive symptoms, and schizotypal and paranoid personality traits.…”
Section: Section 7 Validity Of the Mss-bmentioning
confidence: 99%